Erosion Processes and Control - Garcia-Chevesich, Pablo Andres (The University of Arizona., 2009)
This dissertation represents a unique contribution to the Spanish literature of soil erosion. The author of this document has written and published "Procesos y control de la erosion", a textbook about the engineering of soil erosion processes and the design of the most up-to-date methods and products used for erosion control. The text has been presented in Appendix A.Besides the above, the author of this dissertation is an active committee member at the International Erosion Control Association (IECA), specifically the International Development and the SOIL Fund programs. IECA members are drawn from individuals and erosion control business of different sizes. However, there was a lack of knowledge within IECA members about the formation of post-fire water repellent layers. For instance, Appendix B is represented by an article written by the author of this document, published in Environmental Connection (Volume 2, Issue 3), on July of 2008. The article gives a general description of what post-fire water repellency is, how is it formed, what factors affect it, its consequences on soil erosion, and how to control soil erosion on an efficient way when such a layer has been formed as a consequence of fire.Finally, Appendix C is a research paper in process of submission to the International Journal of Wildland Fire, about the formation of post-fire water repellent layers on Chilean Monterrey pine plantations. Since water repellent layers following wildfires have never been documented on Chilean soils, the need for such a publication is urgent, because Chilean land managers have been ignorant of such phenomenon.